PERKEMBANGAN AKHLAK PESERTA DIDIK DI ERA GENERASI ALPHA - Nadia Shabrina; Septi Triamryaningsih; Nilfa Zalukhu; Aljah Raini; Pani Akhiruddin Siregar (LPPM UM Metro, 2024)
The rapid development of technology greatly affects students in the era of the alpha generation, especially in the aspect of morals, so that guidance is needed in dealing with technological developments by fostering morals. This research was done with the aim of deepening understanding of the methods that can be used to foster the morals of students in the era of the alpha generation. This research uses a qualitative approach with a library research method. The results and discussion obtained show that technology that can access thousands of pieces of information with one finger has resulted in the alpha generation being accustomed to instant things and having critical thinking because they get various kinds of information very easily. The alpha generation needs a wise attitude from adults to guide and foster them for such rapid changes so that they become a generation that is able to utilize this sophistication as a positive thing instead of becoming an individual figure who is indifferent. The conclusion is that moral development is needed by using methods that are in accordance with the character of the alpha generation so that they have morals that are in line with religious and social values. The methods that can be used include giving good examples, making good habits, giving advice, giving special attention, giving punishment, and the storytelling method.